The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1182/blood.v88.3.1052.bloodjournal8831052
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on cellular and molecular mechanisms of arsenic trioxide (As2O3) in the treatment of acute promyelocytic leukemia: As2O3 induces NB4 cell apoptosis with downregulation of Bcl-2 expression and modulation of PML-RAR alpha/PML proteins

Abstract: It has been shown recently in China that arsenic trioxide (As2O3) is a very effective treatment for acute promyelocytic leukemia (APL). APL patients resistant to all-trans retinoic acid (ATRA) and conventional chemotherapy can still respond to AS2O3. In this study, we addressed the possible cellular and molecular mechanisms of this treatment by using NB4 cells as a model. The results show that: (1) As2O3 triggers relatively specific NB4 cell apoptosis at micromolar concentration, as proved by morphology, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 3 publications
9
136
0
1
Order By: Relevance
“…It was shown recently that PML (promyelocytic leukaemia protein) is an in vivo target of human RNF4 [72]. Many cases of APL (acute promyelocytic leukaemia) are caused by a chromosomal translocation that fuses PML to the RAR (retinoic acid receptor), and it was discovered that treatment of APL cells with arsenic caused ubiquitin-mediated degradation of PML-RAR [73][74][75][76][77][78]. Remarkably, the down-regulation of PML-RAR by arsenic did not occur in cells lacking RNF4 [72,79].…”
Section: The Slx5-slx8 Complex Is a Sumo-targeted Ubiquitin Ligasementioning
confidence: 99%
“…It was shown recently that PML (promyelocytic leukaemia protein) is an in vivo target of human RNF4 [72]. Many cases of APL (acute promyelocytic leukaemia) are caused by a chromosomal translocation that fuses PML to the RAR (retinoic acid receptor), and it was discovered that treatment of APL cells with arsenic caused ubiquitin-mediated degradation of PML-RAR [73][74][75][76][77][78]. Remarkably, the down-regulation of PML-RAR by arsenic did not occur in cells lacking RNF4 [72,79].…”
Section: The Slx5-slx8 Complex Is a Sumo-targeted Ubiquitin Ligasementioning
confidence: 99%
“…Complete remission rate and long-term survival rate are high and the relapse rate is low in APL patients treated with As 2 O 3 [8][9][10] . The main mechanism of As 2 O 3 is to induce apoptosis of leukemia cells, which is different from all-trans retinoic acid (ATRA) [11][12][13][14][15][16][17][18][19][20][21][22][23] . Based on the achievements, the experimental studies on anti-tumor effect of As 2 O 3 in such hematopathy as malignant lymphoma [24] and myeloma [25,26] and solide tumors such as cancers of lung [27] , esophagus [28] , stomach [29][30][31][32] , colone [33][34][35] pancreas [36] , mamma [37] , cervix [38] and neuroblastoma [39] are in the ascendant.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, Sun and his colleagues (Sun et al 1992) showed that intravenous infusions of Ailing-1, a crude solution composed of 1% ATO with a trace amount of mercury chloride, induced CR in two-thirds of patients with APL with an impressive 10-year survival rate (30%). In 1996-1997, the SIH reported studies of pure ATO being used to treat relapsed APL (Chen et al 1996(Chen et al , 1997Shen et al 1997). In these studies, 15 relapse patients who previously achieved CR by ATRA-containing treatment were intravenously administered with ATO at a dose of 0.16 mg kg K1 d K1 for 28-54 days.…”
Section: (A) Chemotherapeutic Agentsmentioning
confidence: 99%
“…With regard to the mechanisms underlying ATOtriggered APL cell apoptosis, a number of events can be important: downregulation of Bcl-2 (Chen et al 1996) which cooperates with PML-RARa to block neutrophil differentiation (Kogan et al 2001), collapse of mitochondrial transmembrane potentials (MTP) in a thioldependent manner (Zhu et al 1999b;Chen et al 2001), activation of caspases (Soignet et al 1998;Huang et al 1999) and modulation of PML (Zhu et al 1997). Interestingly, increased PML phosphorylation seems to be associated with increased sumoylation of PML and increased PML-mediated apoptosis.…”
Section: Mechanism Of Action Of Arsenic Trioxide Therapy In Acute Promentioning
confidence: 99%